2017
DOI: 10.3928/01477447-20170810-03
|View full text |Cite
|
Sign up to set email alerts
|

Provider-Initiated Patient Satisfaction Reporting Yields Improved Physician Ratings Relative to Online Rating Websites

Abstract: Recently, providers have begun to publicly report the results of patient satisfaction surveys from their practices. However, these outcomes have never been compared with the findings of commercial online physician rating websites. The goals of the current study were to (1) compare overall patient satisfaction ratings for orthopedic surgeons derived from provider-based third-party surveys with existing commercial physician rating websites and (2) determine the association between patient ratings and provider ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…26 Ricciardi and colleagues compared publicly available internal ratings with online ratings for 415 orthopaedic surgeons, although no overall correlation was calculated. 25 Critics of online physician ratings also point out that the individuals who choose to submit reviews online may not be representative of the general population. For example, prior research has suggested that younger individuals may be more likely to leave online reviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Ricciardi and colleagues compared publicly available internal ratings with online ratings for 415 orthopaedic surgeons, although no overall correlation was calculated. 25 Critics of online physician ratings also point out that the individuals who choose to submit reviews online may not be representative of the general population. For example, prior research has suggested that younger individuals may be more likely to leave online reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Given that these internal ratings are based on validated survey methodologies and include a large number of responses solicited from a broad and random sample of the patient population, it is possible that they could provide a better estimate of each physician's actual patient satisfaction rating. While some prior reports have sought to assess the correlation between online and internal physician ratings, these have primarily been small-scale studies of academic physicians that were restricted to a limited number of websites 24 or a single subspecialty, 25 institution, 26 or department. 27 In this study, we sought to determine the extent to which publicly available online ratings of physicians, which are typically based on a small number of unsolicited reviews, correlate with internal patient-submitted ratings from a large integrated healthcare delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Many health systems also post patients’ narrative responses to open-ended questions (eg, “What did this clinician do well?” and “What could this clinician do better?”). Although these initiatives have received attention in both the medical and lay press [11,12], there has been only one description of the phenomenon in the medical literature [13]. The number of US health systems that are participating in these efforts is unknown, the content of reviews on health systems’ sites has not been described (nor has it been compared to the previously existing narrative content about physicians reviews on commercial rating websites), and the implications for patient experience and quality improvement activities have yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…"Have not heard of this" was an additional answer choice). The online resources physicians were asked to evaluate included: commercial physician rating websites (for-profit sites that are available to the public and allow patients to read and/ or write quantitative and narrative reviews about physicians) 10,11 ; health systems' websites (hospitals and health systems websites that compile and report physician-level data, most commonly ratings and comments drawn from the Consumer Assessment of Healthcare Providers and Systems [CAHPS] surveys) 13 ; individual practices' websites (any website that is created and maintained by an individual practice, which may or may not report data on physician quality or patient experience) 3,17 ; the Rhode Island Department of Health's Find a Doctor tool 18 (which includes data on board certification, hospital privileges, address information, disciplinary actions, and quality metrics that are related to use of health information technology); Medicare public reporting websites (which include practice-level performance data but minimal data on individual physician quality or experience metrics) 19 ; nonprofit physician quality websites (e.g., organizations that report practice-or physician-level data about quality or experience data separately from RIDOH) 20 ; and insurance subscriber portals (insurance company sites that include information on in-network status and, in some cases, quality and experience data). We included links to examples of each type of site within the survey.…”
Section: Development and Description Of Questionsmentioning
confidence: 99%
“…1 To find information about physicians, patients may look to commercial physician rating websites, government-sponsored websites, independently sponsored public reporting organizations, health system sites, insurance companies portals, and others. [1][2][3][4][5][6][7][8][9][10][11][12][13] Although patient use of websites that report publicly reported quality metrics remains minimal, 14 patients may be more likely to seek out online reviews about physicians or health systems. 15 Commercial physician rating websites, for example, are viewed millions of times per month, and there have been rapid increases in numbers of patient reviews on these sites.…”
Section: Introductionmentioning
confidence: 99%